Reproductive and Physiological Responses and Egg Quality Traits of Isa Brown Chickens fed Diets fed Ginger or Turmeric Powder under Tropical Hot Environments - Kujero, Mayowa; Adeyemi, O.A.; Njoku, Chiemeka; Sogunle, Olajide; Sobayo, Richard; Oke, Oyegunle Emmanuel (Archives of Veterinary Science, 2024)
The increasing demand for healthy and low-fat poultry products by consumers has necessitated the use of natural growth promoters to enhance hens’ laying performance. This study investigated the reproductive response and egg quality traits of pullet chickens fed dietary turmeric (Curcuma longa) and ginger (Zingiber officinale) powder. Four hundred and twenty egg-type chicks of Isa Brown at three weeks old were assigned to 5 treatments: basal diet (G0); basal diet supplemented with 1.5 % (G1.5) or 3% (G3) ginger or 1.5(T1.5) or 3% (T3) turmeric during a 60 week trial period. A complete randomized design arrangement was applied. The results showed that the best (p<0.05) hen-day production, hen-housed production, egg mass, feed conversion ratio (FCR), age at first lay and weight at first lay were obtained for birds receiving the 1.5% ginger ration. A higher mortality rate was experienced among the control groups (9.82%), while egg traits revealed significantly higher values of albumen height in hens placed on 1.5 and 3% turmeric powder compared to the other treatment groups. The study concluded that dietary ginger and turmeric enhanced the reproductive performance and egg quality of egg-type chickens over their commercial production lifespan without impairing their overall well-being.